Independent horror games between 2010 and 2020: Selected characteristic features and discernible trends - Marak , Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The focus of this article are independent digital horror games and their characteristics; the goal was to briefly describe the independent horror scene and highlight some of the artistic and technical trends which manifest themselves in the titles belonging to that scene. Due to the sheer number of available games, the scope of the paper is narrowed down to only selected characteristics and trends distinguishable in game texts published between the years 2010 and 2020. The aim of the article is to present a selection of observations and conclusions concerning the independent games scene and to hopefully point to what these games can tell scholars about the way both the players and the developers perceive the horror genre.